BANYAKNYA PENJUALAN BBM DENGAN MENGGUNAKAN POM MINI TANPA DILENGKAPI IZIN DI KECAMATAN MUARA WAHAU KABUPATEN KUTAI TIMUR - Fatimah Asyari, Haris Suyanto dan (Universitas 17 Agustus 1945 Samarinda, 2019)
The development of the economy today is growing rapidly, which has animpact on the lives of people who need fuel oil (BBM) for daily needs fortheir survival. Economic development in general and in the field ofindustry and national trade in particular has produced a variety of goodsand / or services that can be consumed.The emergence of mini pom phenomena is not a few issues that havearisen among the people. The tools that are in mini poms that are sold ingeneral do not deny causing a particular concern. Jakarta Ministry ofTrade recognizes the existence of mini poms violating the rules. But apartfrom legal issues, they urge the public not to buy retail gasoline at themini pump, if it is not forced to due to inaccurate dosing can harmconsumers.the problems in this study are: (1) What is the Legal Position of the sale ofmini pom fuel according to the applicable laws and regulations ?; (2)How is Pertamina Oil Sales Supervision Related to Consumer Protection?The conclusions of this study are: (1) The sale of Pom Mini Fuel is not inaccordance with the Law, because it is not in accordance with thestandards listed in Law Number 2 of 1981 concerning Legal Metrologyand PerBPH Oil and Gas Number 6 years 2015; and (2) As is known,Pom Mini retail oil seller is an illegal and unlawful business activity thatmay be subject to criminal sanctions.